2004
DOI: 10.1177/0272989x04268955
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Biases in Standard Gamble and Time Tradeoff Utilities

Abstract: The standard gamble (SG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 21 publications
4
76
0
1
Order By: Relevance
“…Although this makes sense, it depends on several assumptions, including, as indicated, constant proportional tradeoffs and for instance the absence of discounting. Since the introduction of TTO [6] and its initial development, a considerable body of evidence has emerged showing that these assumptions do not always hold and, consequently, the way TTO is framed may influence the value given to health states [1,[7][8][9]. Therefore, differences in TTO values may arise from lack of standardisation of the TTO procedure.…”
mentioning
confidence: 99%
“…Although this makes sense, it depends on several assumptions, including, as indicated, constant proportional tradeoffs and for instance the absence of discounting. Since the introduction of TTO [6] and its initial development, a considerable body of evidence has emerged showing that these assumptions do not always hold and, consequently, the way TTO is framed may influence the value given to health states [1,[7][8][9]. Therefore, differences in TTO values may arise from lack of standardisation of the TTO procedure.…”
mentioning
confidence: 99%
“…Although the TTO score would decrease, it seems unlikely that there was a change in the patient's underlying quality of life or of their preference for health states. Although the utility function has been described as being concave over time in most people (30,41,42), those who responded in this manner would have a step function for utility over time, which would represent both a range restriction bias and an extreme example of nonconstant proportional TTO. Although other authors have suggested ways to correct TTO scores by adjusting for time preference bias (42), these methods would not apply in our extreme cases.…”
Section: Discussionmentioning
confidence: 99%
“…Health state valuations of current heath states or future potential outcomes provide an assessment of utilities which are considered to be a measure of the preference for current health or for each potential future outcome. [5,6] Although controversy exists about the degree to which the standard gamble or time trade-off may provide more desirable estimates of utility [7], there is general agreement that the scores obtained from the rating scale method do not provide utilities; rather the scores provide only an assessment of preference.…”
Section: Introductionmentioning
confidence: 99%